Development of a Mesoamerican intra-genepool genetic map for QTL detection in a drought tolerant x susceptible common bean (Phaseolus vulgaris L.) cross - Blair, Matthew W.; Galeano, Carlos; Tovar, Eduardo; Muñoz Torres, Mónica Cecilia; Velasco, Alejandro; Beebe, Stephen E.; Rao, Idupulapati M. (Springer, 2012)
Drought is a major constraint to common bean (Phaseolus vulgaris L.) production, especially in developing countries where irrigation for the crop is infrequent. The Mesoamerican genepool is the most widely grown subdivision of common beans that include small red, small cream and black seeded varieties. The objective of this study was to develop a reliable genetic map for a Mesoamerican × Mesoamerican drought tolerant × susceptible cross and to use this map to analyze the inheritance of yield traits under drought and fully irrigated conditions over 3 years of experiments. The source of drought tolerance used in the cross was the cream-seeded advanced line BAT477 crossed with the small red variety DOR364 and the population was made up of recombinant inbred lines in the F5 generation. Quantitative trait loci were detected by composite interval mapping for the traits of overall seed yield, yield per day, 100 seed weight, days to flowering and days to maturity for each field environment consisting of two treatments (irrigated and rainfed) and lattice design experiments with three repetitions for a total of six environments. The genetic map based on amplified fragment length polymorphism and random amplified polymorphic DNA markers was anchored with 60 simple sequence repeat (SSR) markers and had a total map length of 1,087.5 cM across 11 linkage groups covering the whole common bean genome with saturation of one marker every 5.9 cM. Gaps for the genetic map existed on linkage groups b03, b09 and b11 but overall there were only nine gaps larger than 15 cM. All traits were inherited quantitatively, with the greatest number for seed weight followed by yield per day, yield per se, days to flowering and days to maturity. The relevance of these results for breeding common beans is discussed in particular in the light of crop improvement for drought tolerance in the Mesoamerican genepool.